Towards Optimizing Building Material Utilization: Strategies for Mitigating Wastage on Construction Sites in Nigeria - Aule, Thomas Terna; Jide, Anifowose Kamaldeen; Ikharia, Ibrahim Saliu; Tijjani, Ishaq Nuhu; Saleem , Abubakar Fagam; Aule, Solomon Iorfa (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The construction industry significantly contributes to economic development but is also a major source of material waste, which escalates costs and harms the environment. This study investigates the factors contributing to material waste on construction sites and explores mitigation strategies. The research adopts a quantitative approach using a cross-sectional survey of construction professionals in Kaduna, Nigeria. A structured questionnaire, utilizing a five-point Likert scale, was administered to a sample of 105 respondents, and data were analysed using descriptive statistics and NVivo 15 for qualitative insights. The findings reveal that design inefficiencies, site mismanagement, poor workforce training, and logistical issues are key contributors to material waste. Design changes during construction (73%), defective site instructions (66%), and complex designs (71%) were identified as major factors. Additionally, poor worker attitudes (65%), inadequate training (65%), and non-standard material sizes (90%) exacerbate waste. Environmental influences, including adverse weather conditions (64%) and site topography (72%), also play significant roles. To minimize waste, respondents emphasized proper material handling, improved design processes, site supervision, and enhanced storage practices. This study highlights the need for integrated waste reduction strategies in construction. However, further research is needed to explore technological interventions such as digital modelling and automation for waste minimization. The findings contribute to advancing sustainable construction practices by promoting resource efficiency and environmental responsibility.